2013
DOI: 10.1007/s13402-013-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of familial breast cancer with undetected BRCA1 and BRCA2 mutations: clinical implications

Abstract: Current evidence suggests that in the majority of cases with BRCA1 and BRCA2 negative familial breast cancer the etiology is due to interactions of intermediate or low risk alleles with environmental and lifestyle factors. Thus, a careful selection of patients submitted to genetic testing is needed. Clearly, further research is required to fully elucidate the etiology of non-BRCA familial breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…In breast cancer, genes directly affected by hypermethylation include tumor suppressor genes (BRCA1), metastasisinhibitory genes (CDH1, TIMP-3), hormone receptor genes (ER-α, PR) and cell cycle control genes [p16INK4a (CDKN2A)]. 22 , 23 Methylation of the BRCA1 promoter has been shown to occur in approximately 20% of breast cancer patients. Sporadic tumours with BRCA1 promoter methylation have been reported to be ER and PR negative.…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer, genes directly affected by hypermethylation include tumor suppressor genes (BRCA1), metastasisinhibitory genes (CDH1, TIMP-3), hormone receptor genes (ER-α, PR) and cell cycle control genes [p16INK4a (CDKN2A)]. 22 , 23 Methylation of the BRCA1 promoter has been shown to occur in approximately 20% of breast cancer patients. Sporadic tumours with BRCA1 promoter methylation have been reported to be ER and PR negative.…”
Section: Resultsmentioning
confidence: 99%
“…An estimated 5–10% of all breast cancers are associated with hereditary risk . Familial aggregation of breast cancer in women below age 51 years is mainly due to heritable causes .…”
mentioning
confidence: 99%
“…Familial aggregation of breast cancer in women below age 51 years is mainly due to heritable causes . Germline mutations in the BRCA1/2 genes are found in approximately 30% of patients with the family risk . However, the status of HR and other DNA repair pathways in the tumor cells of the remaining vast majority of hereditary breast cancers, particularly hereditary TNBCs, is unknown.…”
mentioning
confidence: 99%
“…It is also reported that most of the families with <6 breast cancer cases and no ovarian cancer do not carry BRCA1 /2 mutations that can be detected by routine sequencing protocols. [7] Various mutations including nonsense mutations, small deletions and insertions, and large genomic rearrangements (LGRs) are reported in BRCA1 gene. [8] Furthermore, these mutations can result in recurrent mutations of other specific genes (such as RB1) that may lead to other cancers.…”
Section: Introductionmentioning
confidence: 99%